Effect of river morphology in Sungai Jemberau at Tasik Chini due to upland activities - Abdul Razak, Mohamad Ghazi (2017)
Study on river morphology was conducted at Sungai Jemberau, Pahang. This study focused on changes of river morphology by determine the problems based on the changes of morphology at specific location and to interpret the responsible factors that caused the changes of river morphology. Several stages and approaches have been used. First, it involves the phase of planning studies and literature. Secondly, it is an approach used for data collection and information followed by the implementation of learning techniques. The study area is about the river in Tasik Chini catchment area. Expected results for morphology changes are collected and analysis from the Google Earth Maps. From the Google Earth Maps, the changes of river can be seen from year 2010 until year 2017. There are several stage records available in the study. Cross-section across river channel of the river is used to identify all changes of river morphology In year 2017. This study was carried out to identify the river characteristic of the factor affecting erosion occurs and the changes of cross sectional area . Besides that, it can be used to identify the problem based on the changes of morphology at specific location. Other than that, it can be used by other parties to make reference in their research. Lastly, local authorities can implemented appropriate solution to reduce the flood event's risks.